Unlocking research: Parental engagement in children's learning - Janet Goodall (The research-informed Teaching Revolution: Early Years, 2021)
This chapter aims to support early years practitioners to access, and use, research around parental engagement in children's learning. The chapter covers barriers to being research informed (such as time, access to publications), what being research informed would look like, and includes tips for practitioners.